Multi‐instrument characterization of the surfaces and materials in microfabricated, carbon nanotube‐templated thin layer chromatography plates. An analogy to 'The Blind Men and the Elephant'. (18th April 2013) - Jensen, David S.; Kanyal, Supriya S.; Madaan, Nitesh; Hancock, Jared M.; Dadson, Andrew E.; Vail, Michael A.; Vanfleet, Richard; Shutthanandan, V.; Zhu, Zihua; Engelhard, Mark H.; Linford, Matthew R.
<x xml:space="preserve">Abstract</x> We apply a suite of analytical tools to characterize materials created in the production of microfabricated thin layer chromatography plates. Techniques used include X‐ray photoelectron spectroscopy (XPS), valence band spectroscopy, time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) in both positive and negative ion modes, Rutherford backscattering spectroscopy (RBS), and helium ion microscopy. Materials characterized include: the Si(100) substrate with native oxide: Si/SiO2, alumina (35 nm) deposited as a diffusion barrier on the Si/SiO2: Si/SiO2/Al2O3, iron (6 nm) thermally evaporated on the Al2O3: Si/SiO2/Al2O3/Fe, the iron film annealed in H2 to make Fe catalyst nanoparticles: Si/SiO2/Al2O3/Fe(NP), and carbon nanotubes (CNTs) grown from the Fe nanoparticles: Si/SiO2/Al2O3/Fe(NP)/CNT. The Fe films and nanoparticles appear in an oxidized state. Some of the analyses of the CNTs/CNT forests appear to be unique: (i) the CNT forest appears to exhibit an interesting 'channeling' phenomenon by RBS, (ii) we observe an odd–even effect in the SIMS spectra of Cn‐ species for n = 1 – 6, with the n ≥ 6 ions showing a steady decrease in intensity, and (iii) valence band characterization of CNTs using X‐radiation is reported. Initial analysis of the CNT forest by XPS shows that it is 100 at.% carbon. After one year, only ca. 0.25 at.% oxygen is observed. The information obtained from the combination of the different analytical tools provides a more complete understanding of our materials than a single technique, which is analogous to the story of 'The Blind Men and the Elephant'. The raw XPS and ToF‐SIMS spectra from this study will be submitted to Surface Science Spectra for archiving. Copyright © 2013 John Wiley & Sons, Ltd.